-51=-3h

Simple and best practice solution for -51=-3h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -51=-3h equation:


Simplifying
-51 = -3h

Solving
-51 = -3h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '3h' to each side of the equation.
-51 + 3h = -3h + 3h

Combine like terms: -3h + 3h = 0
-51 + 3h = 0

Add '51' to each side of the equation.
-51 + 51 + 3h = 0 + 51

Combine like terms: -51 + 51 = 0
0 + 3h = 0 + 51
3h = 0 + 51

Combine like terms: 0 + 51 = 51
3h = 51

Divide each side by '3'.
h = 17

Simplifying
h = 17

See similar equations:

| 10x-(3x-7)=21 | | 3x+2y=155 | | 9sinx=-6 | | 4(6x+7)=24x-2 | | a*a-11a+18=0 | | 20d/13-12d=-43 | | 8h+5=85 | | 77=2t-13t | | 2x^2+0.25x+0.05=0 | | -5(x-8)+x=40-4x | | 0=45+6x-3x^2 | | 9n*9n+81n=0 | | y=45+6x-3x^2 | | 11/7 | | G/-5=-13 | | M+4(2*m-3)=-3 | | -(5x-14)+2(6x+6)= | | -7x^2+17=-39 | | -3(x-8)=-3x+24 | | -7x^2+17=39 | | 5x-15+6=4x-3 | | 2y+3xy= | | 2(-2k+4y)+6y= | | 12m^2-8m^2=15 | | x-2/7=0 | | 7X=2/X | | 3(x+5)-x=3 | | -7(4x+2)+6x=74 | | ln(9x)=1.4 | | 3x^2-21x-180=0 | | 17r-7=13r+13 | | 145/-66 |

Equations solver categories